PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN,KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI HOTEL PATRA JASA SEMARANG - Fidyah Yuli Ernawati; Sopi Sopi (JURNAL STIE SEMARANG, 2020)
ievement of the target of the Patra Jasa Semarang hotel in the last 3 years. Both profit oriented and social. Hotel Patra Jasa Semarang is also one of the leading hotels in the Central Java region. This success was obtained due to high employee performance. This study aims to determine the effect of work environment, leadership, compensation, motivation on employee performance. The population of this study were 150 employees at the Patra Jasa Semarang Hotel. The sample in this study used the Slovin formula in order to obtain 109 employees of Hotel Patra Jasa Semarang. The results of this study indicate that work environment variables and compensation have a positive and significant effect on employee performance. This is indicated by the results obtained from the partial test (t test) for variable X1 with 0.001 (P <0.05) and variable X3 with a value of 0.006 (P <0.05) and for variables X2 Motivation and X4 Leadership there is no effect. on employee performance. It means that work environment variables and compensation can increase employee performance at Hotel Patrajasa Semarang. The higher the compensation, the higher the performance, and vice versa. For the variable work environment, the better the work environment in that place, the higher the employee performance at Hotel Patra Jasa Semarang. The motivation variable has no effect, it means that high motivation does not necessarily have an impact on employee performance and vice versa, while the leadership variable does not affect employee performance, it means that the better the leadership has less meaning in giving the effect of increasing employee performance at Hotel Patra Jasa Semarang. On the other hand, the lack of good leadership does not have a significant effect on the decline in employee performance at Hotel Patra Jasa Semarang. The conclusion of this study is that there is a positive influence of work environment variables on employee performance, because the P-value of the work environment variable is 0.001 (P <0.05) so that the proposed hypothesis is accepted, there is no influence of leadership variables on employee performance, because the P-value in the leadership variable of 0.451 (P> 0.05) so that the proposed hypothesis is rejected.There is a positive influence of the compensation variable on employee performance, because the P-value of the compensation variable is 0.006 (P <0.05) so that the proposed hypothesis is accepted. the influence of the motivation variable on employee performance, because the P-value of the motivation variable is 0.733 (P> 0.05) so that the proposed hypothesis is rejected.